LOYALITAS KARYAWAN DITINJAU DARI LINGKUNGAN, BUDAYA, MOTIVASI KERJA PADA PERUSAHAAN PERSEORANGAN HARUN KONSTRUKSI DI SUKOHARJO - Muhammad Faiqh Subeki; Eny Kustiyah; Ibnu Suryo; Fithri Setya Marwati (ITB AAS Indonesia Surakarta, 2026)
Employee loyalty is a crucial factor in supporting organizational sustainability, particularly in small-scale business with limited human resources. This study aims to analyze the effect of work environment, organizational culture, and work motivation on employee loyalty at Harun Construction, a sole ownership located in Sukoharjo. This research used quantitative descriptive method. The population in the study amounted to 45 employee of Harun Construction. Saturated sample was used as a sampling technique. Data were collected through questuonnaires, supported by observation, interviews, and documentation. This research uses validity and reliability tests as a instrument test. Normality, multicollinearity, and heteroscedasticity tests as a classical assumption test. Multiple linear regression analysis, F-test, t-test, and coefficient of determination (R2) as hypothesis testing using SPSS26. The result show that work environment, organizational culture, and work motivation simultaneously affect employee loyalty. Partially, employee loyalty is positively and significantly influenced by work environment and organizational culture, while work motivation does not have a significant effect. Keywords : Work Environment, Organizational Culture, Work Motivation and Employee Loyalty.